2023
DOI: 10.1101/2023.03.04.531100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generally-healthy individuals with aberrant bowel movement frequencies show enrichment for microbially-derived blood metabolites associated with reduced kidney function

Abstract: ObiectiveBowel movement frequency (BMF) variation has been linked to changes in the composition of the human gut microbiome and to many chronic conditions, like metabolic disorders, neurodegenerative diseases, chronic kidney disease (CKD), and other intestinal pathologies like irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD). Slow intestinal transit times (constipation) are thought to lead to compromised intestinal barrier integrity and a switch from saccharolytic to proteolytic fermentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 103 publications
1
6
0
Order By: Relevance
“…7 ). In a recent study, we observed a similar association between PTRs and bowel movement frequency (BMF) in another independent cohort, where PTRs appeared to increase with increasing BMF 58 . Overall, our results reveal a promising approach to inferring in situ growth phases for abundant organisms detected in human gut metagenomic time series.…”
Section: Discussionsupporting
confidence: 68%
“…7 ). In a recent study, we observed a similar association between PTRs and bowel movement frequency (BMF) in another independent cohort, where PTRs appeared to increase with increasing BMF 58 . Overall, our results reveal a promising approach to inferring in situ growth phases for abundant organisms detected in human gut metagenomic time series.…”
Section: Discussionsupporting
confidence: 68%
“…The biological experiment was implemented according to the randomised complete design CRD, and the analysis of variance was carried out using the General Linear Model within the SAS (Hefny, Awad and Youssef 2023) program. When there were significant differences between the means, Duncan's test (Johnson et al 2023) was used to determine the significance of the differences between the different means at a probability level of 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics, especially bacterial species from Lactobacillus or Bifid bacterium, are considered the most important and preferred options for treating diarrhoea due to their ability to improve intestinal function (Jassim, 2021 ), strengthen the immune system to fight infections, and improve digestion and nutrient absorption. It may also reduce intestinal irritation and inflammation, 2022; Johnson et al, 2023;Mohammed, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that individuals with increased colonic transit time have phenylacetylglutamine in their urine . Elevated levels of PAGln among healthy individuals are related with high bowel movement frequency, which might also drive long-term chronic disease risk . Increased phenylalanine metabolism is also seen among patients with panic disorders .…”
Section: Pagln In Neurological Disordersmentioning
confidence: 99%
“… 69 Elevated levels of PAGln among healthy individuals are related with high bowel movement frequency, which might also drive long-term chronic disease risk. 70 Increased phenylalanine metabolism is also seen among patients with panic disorders. 71 Decreased plasma levels of phenylalanine are seen to be associated with a risk for mild cognitive impairment in Alzheimer’s disease.…”
Section: Pagln In Neurological Disordersmentioning
confidence: 99%